Professor Dato' Dr. Rosli shared knowledge on the function of ultrasound in engineering - UMP, PNC
Professor Dato' Dr. Rosli Mohd Yunus of the Faculty of Chemical & Natural Resources Engineering (FKKSA) recnetly shared his experience and findings relating to using ultrasound to increase engineering separation process in distillation, membrane filtration and extraction.